O Debate previdenciário e as implicações macroeconômicas: uma análise da literatura especializada no período recente - REGO, Jessé Sales (2016)
The present dissertation aims to present the social security debate in Brazil, in the World and its macroeconomic implications. The choice for this theme is justified by the absence of studies that, in addition to the technical aspects behind social security systems, present together historical, philosophical and, above all, political economy questions. For this, the debate is classified into two main categories: the conservative perspective and the perspective of the demand for social security. In addition, the debate in Brazil is focused on the macroeconomic controversies and on the relationship between social security spending and fiscal equilibrium.